Acid-Induced Aggregation and Gelation of Bovine Sodium Caseinate-Carboxymethylcellulose Mixtures - Hidalgo, María Eugenia; Riquelme, Bibiana D.; Alvarez, Estela M.; Wagner, Jorge R.; Risso, Patricia H. (IntechOpen, 2012)
None